Relationship of UV exposure to prevalence of multiple sclerosis in England. - Ramagopalan, S; Handel, A; Giovannoni, G; Rutherford Siegel, S; Ebers, G; Chaplin, G (2011)
OBJECTIVE: To assess the potential relationship of ultraviolet B radiation (UVB) and Epstein-Barr virus (EBV) exposure in explaining the period prevalence of multiple sclerosis (MS) in England. METHODS: English national Hospital Episode Statistics covering all admissions to National Health Service hospitals in England in the 7 years from 1998 to 2005 were used to obtain the period prevalences of MS and infectious mononucleosis (IM) in England. The United States National Aeronautics and Space Administration's data on UVB intensity for England from the Nimbus 7 satellite was collected. The relationships among the 3 variables (MS prevalence, IM prevalence, and UVB intensity) were investigated. RESULTS: The regression of MS against UVB intensity for all seasons had an r(2) of 0.61; when including the interaction of IM with seasonal UVB, the r(2) rose to 0.72. CONCLUSIONS: UVB exposure and IM together can explain a substantial proportion of the variance of MS. The effect of UVB on generating vitamin D seems the most likely candidate for explaining its relationship with MS. There is a pressing need to investigate the role of vitamin D and EBV and how they might interact to influence MS risk to identify potential prevention strategies.